The athlete's guide to making weight - Macedonio, Michele A. (Human Kinetics, 2009)
Moving up or down a weight class? Switching positions within your sport? Competing in a new league or level? Are you big enough, quick enough, and strong enough? Elite athletes understand the impact that body weight and composition have on performance. Gain too much, and lose that all-important first step. Drop too much, and risk being overpowered. Here, sport dietitians Macedonio and Dunford have analyzed today's top athletes, competitive trends, and positional demands across 21 sports to help you determine--and achieve--your optimal competitive weight. Assess body composition, nutritional requirements, and your current training program. Then follow the customizable meal plans for a personalized approach to maximizing performance. Whether you need to add muscle and mass, lose body fat, or control water weight, this book will help you reach your goals without sacrificing safety or performance.--From publisher description.